2020
DOI: 10.1039/d0fo00911c
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil extracted from Coregonus peled improves obese phenotype and changes gut microbiota in a high-fat diet-induced mouse model of recurrent obesity

Abstract: The potential modulatory effect of fish oil from Coregonus peled on recurrent obese mice by influencing persistent microbiome alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
7
1
Order By: Relevance
“…Many studies have demonstrated that marine unsaturated lipids can positively regulate the gut microbiota of rats. [ 31 ] In line with previous studies, the dominant bacteria of the samples were Bacteroidetes and Firmicutes . [ 32–34 ] The family Bacillariophyceae is thought to be associated with obesity, fatty liver, and intestinal health because of metabolic processes associated with butyric and acetic acids in species and families of microorganisms of this bacterium.…”
Section: Discussionsupporting
confidence: 83%
“…Many studies have demonstrated that marine unsaturated lipids can positively regulate the gut microbiota of rats. [ 31 ] In line with previous studies, the dominant bacteria of the samples were Bacteroidetes and Firmicutes . [ 32–34 ] The family Bacillariophyceae is thought to be associated with obesity, fatty liver, and intestinal health because of metabolic processes associated with butyric and acetic acids in species and families of microorganisms of this bacterium.…”
Section: Discussionsupporting
confidence: 83%
“…The variable V3/4 region of 16 S rRNA gene was amplified with following primers 319F (5′-ACTCCTACGGGAGGCAGCAG-3′) and 806R (5′-GGACTACHVGGGTWTCTAAT-3′). The PCR products were purified with AMPure XP beads (Beckman Coulter, Indianapolis, IN), quantified by the PicoGreen dsDNA assay kit, and sequenced using Illumina HiSeq 4000 with 2 × 300 bp paired-end reads as previous reported method [ 22 ]. For operational taxonomic units (OTUs), nucleotide sequence with 97% identity was assigned to the same OTUs based on SILVA128 database.…”
Section: Methodsmentioning
confidence: 99%
“…Diet supplementation with fish-derived oil containing omega 3 fatty acids has been shown to possess beneficial effects in diabetes and obesity [ 13 ]. Different types of extracts from fish have been tested for beneficial action on obesity and type 2 diabetes, such as tuna-derived extracts through boiling [ 14 ], Tapra fish-derived fish oil [ 15 ], or ethanol extracts from Masou salmon [ 16 ].…”
Section: Introductionmentioning
confidence: 99%